Relation of electricity to farmers - Davis, Tomas Clarke (My University, 1891)
Introduction: Of the present graduating class only ten percent intend to follow farming as a means of obtaining a living. The old question which is never fully answered, is, why do not more of the educated class follow agriculture. I do not wish it understood I intend to answer it here, but like writers who seem to think that they have satisfactorily settled the question, I intend only to show how more inducements may be held out to those choosing an occupation. A man should not choose an occupation if he thinks he would not be suited to that occupation, but I think that farming may be improved so that it will be looked upon more favorably.
Citation: Davis, Tomas Clarke. Relation of electricity to farmers. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Electricity; Agriculture; Farmer; Modernization; Theses; Manuscripts (documents)